2015
DOI: 10.1080/09500340.2015.1061062
|View full text |Cite
|
Sign up to set email alerts
|

Tunable THz optical bistability in graphene-based heterostructures

Abstract: We investigate theoretically the THz optical bistability properties of graphene-based heterostructures. We derive a simple procedure to calculate the nonlinear transmission in graphene-based heterostructures. It is found that the hysteretic response occurs when the frequency of the incident light is less than critical frequency. Compared with the traditional nonlinear materials, THz optical bistability can be tuned more effectively in the proposed structure. It is shown that the optical bistability can be elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Moreover, it has been shown that the linear dispersion properties of graphene should result in strong nonlinear optical behavior at the microwave and THz frequencies [20,21]. Consequently, nonlinear phenomena such as optical bistability have recently been studied for several graphene-based materials in order to achieve low thresholds and efficient optical control at the THz frequencies [22][23][24][25][26]. Specifically, the optical bistability has theoretically been investigated for graphene-wrapped dielectric composite at THz frequencies.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it has been shown that the linear dispersion properties of graphene should result in strong nonlinear optical behavior at the microwave and THz frequencies [20,21]. Consequently, nonlinear phenomena such as optical bistability have recently been studied for several graphene-based materials in order to achieve low thresholds and efficient optical control at the THz frequencies [22][23][24][25][26]. Specifically, the optical bistability has theoretically been investigated for graphene-wrapped dielectric composite at THz frequencies.…”
Section: Introductionmentioning
confidence: 99%
“…The working frequency is 𝑓 = 𝜔/2𝜋 = 0.34 THz. [20] It is well known that for a dielectric silica without graphene, there is a Brewster angle for the TM wave given by tan(𝜃 B ) = √ 𝜀 2 , at which the reflected light vanishes (see the red dashed line in Fig. 2(a)).…”
mentioning
confidence: 96%